2017
DOI: 10.1055/s-0043-114670
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin for Cognitive Deficits Associated with Schizophrenia, Bipolar Disorder, and Major Depression: A Systematic Review

Abstract: CRD42017058094.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…In the last 20 years, erythropoietin (EPO) has emerged as a potential candidate for neuroprotective and neuroregenerative treatment in injury and disease of the nervous system (Sargin et al, 2010 ). Interestingly, EPO improves cognitive performance in healthy animals and humans and in disease, including in MS (Ehrenreich et al, 2007 ; Robinson et al, 2018 ; Li et al, 2018 ). Although the mechanism is still largely unknown, we and others showed that EPO acts directly on OLs to increase myelination in vitro and in vivo (Sugawa et al, 2002 ; Cervellini et al, 2013 ; Hassouna et al, 2016 ; Gyetvai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, erythropoietin (EPO) has emerged as a potential candidate for neuroprotective and neuroregenerative treatment in injury and disease of the nervous system (Sargin et al, 2010 ). Interestingly, EPO improves cognitive performance in healthy animals and humans and in disease, including in MS (Ehrenreich et al, 2007 ; Robinson et al, 2018 ; Li et al, 2018 ). Although the mechanism is still largely unknown, we and others showed that EPO acts directly on OLs to increase myelination in vitro and in vivo (Sugawa et al, 2002 ; Cervellini et al, 2013 ; Hassouna et al, 2016 ; Gyetvai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in healthy and depressed individuals showed that, similar to the effects seen with conventional antidepressants, EPO reduces the neurocognitive processing of negative emotional information while concurrently improving cognitive function (Miskowiak et al, 2008(Miskowiak et al, , 2010. More recently, a meta-analysis determined that EPO alleviates the cognitive deficits associated with bipolar disorder, major depression, and schizophrenia without producing a significant unfavorable impact (Li et al, 2018). These beneficial effects of EPO are consistent with EPO's ability to regulate the activity of HPA axis (Tringali et al, 2007;Dey and Noguchi, 2017;Dey et al, 2020).…”
Section: Epo and The Regulation Of Stress And Respiratory Controlmentioning
confidence: 80%
“…For instance, EPO appears to induce the production of brain-derived neurotrophic factor (BDNF) in the hippocampal tissue. In addition, in patients with schizophrenia, a decrease of S100 proteina marker for glial damagepredicted a better clinical outcome after one month of treatment [434,438,440,441]. Studies with mice receiving EPO showed an increase of LTP in the hippocampus.…”
Section: Erythropoietinmentioning
confidence: 98%